CD34+CD146+ adipose-derived stromal cells enhance engraftment of transplanted fat. (15th June 2020) - Borrelli, Mimi R.; Patel, Ronak A.; Blackshear, Charles; Vistnes, Stephanie; Diaz Deleon, Nestor M.; Adem, Sandeep; Shen, Abra H.; Sokol, Jan; Momeni, Arash; Nguyen, Dung; Longaker, Michael T.; Wan, Derrick C.
Abstract: Fat grafting is a surgical technique able to reconstruct and regenerate soft tissue. The adipose-derived stromal cells (ASCs) within the stromal vascular fraction are believed to drive these beneficial effects. ASCs are increasingly recognized to be a heterogeneous group, comprised of multiple stem and progenitor subpopulations with distinct functions. We hypothesized the existence of an ASC subpopulation with enhanced angiogenic potential. Human ASCs that were CD34+CD146+, CD34+CD146−, or CD34+ unfractionated (UF) were isolated by flow cytometry for comparison of expression of proangiogenic factors and endothelial tube-forming potential. Next, lipoaspirate was enriched with either CD34+CD146+, CD34+CD146−, CD34+ UF ASCs, or was not enriched, and grafted beneath the scalp skin of immunodeficient CD-1 Nude mice (10 000 cells/200 μL/graft). Fat retention was monitored radiographically more than 8 weeks and fat grafts were harvested for histological assessment of quality and vascularization. The CD34+CD146+ subpopulation comprised 30% of ASCs, and exhibited increased expression of vascular endothelial growth factor and angiopoietin-1 compared to CD34+CD146− and CD34+ UF ASCs, and increased expression of fibroblast growth factor-2 compared to CD34+CD146− ASCs. The CD34+CD146+ subpopulation exhibited enhanced induction of tube-formation compared to CD34+CD146− ASCs. Upon transplantation, fat enriched CD34+CD146+ ASCs underwent less resorption and had improved histologic quality and vascularization. We have identified a subpopulation of CD34+ ASCs with enhanced angiogenic effects in vitro and in vivo, likely mediated by increased expression of potent proangiogenic factors. These findings suggest that enriching lipoaspirate with CD34+CD146+ ASCs may enhance fat graft vascularization and retention in the clinical setting. : Abstract : CD146+ adipose-derived stromal cells express increased levels of proangiogenic factors VEGF, ANGPT1, FGF and enhance tube-formation by vascular endothelial cells. Fat grafts enriched this subpopulation also undergo the least resorption and possess improved histologic quality and vascularization. Enriching lipoaspirate with CD146+ ASCs may enhance fat graft retention in the clinical setting.